Quality controlled ECG data compression based on 2D discrete cosine coefficient filtering and iterative JPEG2000 encoding. (February 2020) - Pandey, Anukul; Singh Saini, Barjinder; Singh, Butta; Sood, Neetu
Graphical abstract: Highlights: Exploitation of inter and intra block correlation for 2D ECG data compression. Quality controlled ECG compression using filtering and iterative JPEG2000 encoding. The proposed technique is validated on the single and multi-lead ECG system. Abstract: This paper presents a quality controlled reconstruction of ECG signal by the formulation of 2D Discrete Cosine Transform (DCT) coefficient and iterative JPEG2000 encoding scheme for Electrocardiogram (ECG) data compression. It employs variable blockwise ( L = 32 to 2048 samples ) DCT to exploit inter and intra-beat correlation inherent in ECG. The Regula-Falsi method is applied to obtain the optimal threshold for the DCT coefficients, which are stacked row-wise in order to form a 2D DCT coefficient array for the correlation analysis. Afterwards, window-based filtering is applied to retain the significant DCT coefficients with varying window size ( ws ). Differential pulse code modulation based quantization scheme is then applied to 2D DCT coefficients array in order to make it conformal to JPEG2000 encoding. Finally, iterative JPEG2000 encoding is utilized for achieving the overall predefined reconstruction error. The experimentations were performed on all the 48 records of Massachusetts Institute of Technology-Beth Israel Hospital (MIT-BIH) arrhythmia database. The proposed method provides compression ratio = 39.48 & 40.18; percentage root mean square difference = 2.02 & 2.06 and the quality score = 19.45 & 19.56 at ws = 50% & 20% respectively for L = 256. The proposed technique results were also validated on all records of four standard ECG databases including i) MIT-BIH Normal sinus rhythm ii) CU ventricular tachyarrhythmia iii) CSE and iv) PTB Database. Further, a comparative analysis between the proposed method and some recent existing works was also performed. The results clearly demonstrate the superiority of proposed method.